2019
DOI: 10.1111/nyas.14213
|View full text |Cite
|
Sign up to set email alerts
|

Between persistently active and activity‐silent frameworks: novel vistas on the cellular basis of working memory

Abstract: Recent work has revealed important new discoveries on the cellular mechanisms of working memory (WM). These findings have motivated several seemingly conflicting theories on the mechanisms of short‐term memory maintenance. Here, we summarize the key insights gained from these new experiments and critically evaluate them in light of three hypotheses: classical persistent activity, activity‐silent, and dynamic coding. The experiments discussed include the first direct demonstration of persistently active neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 70 publications
(191 reference statements)
5
69
0
Order By: Relevance
“…Finally, we consider the proposal that functionally active states are supported by elevated neural activity, whereas functionally latent states correspond to activity-silent mnemonic mechanisms. This distinction has been suggested by a number of authors (e.g., Kamiński & Rutishauser, 2019;LaRocque et al, 2013LaRocque et al, , 2015Lewis-Peacock et al, 2012;Manohar et al, 2019;Olivers et al, 2011;Stokes, 2015). In the framework developed here, this division of labour is only helpful if it confers differential functional properties on active and latent WMs.…”
Section: Separation By Neurophysiological Mechanismmentioning
confidence: 91%
“…Finally, we consider the proposal that functionally active states are supported by elevated neural activity, whereas functionally latent states correspond to activity-silent mnemonic mechanisms. This distinction has been suggested by a number of authors (e.g., Kamiński & Rutishauser, 2019;LaRocque et al, 2013LaRocque et al, , 2015Lewis-Peacock et al, 2012;Manohar et al, 2019;Olivers et al, 2011;Stokes, 2015). In the framework developed here, this division of labour is only helpful if it confers differential functional properties on active and latent WMs.…”
Section: Separation By Neurophysiological Mechanismmentioning
confidence: 91%
“…Updating and maintaining working memory content requires collaboration between multiple areas in the brain. Core neural structures are located in the posterior parietal cortex and prefrontal cortex, while the role of the MTL is unclear (for reviews see (5, 6)). The posterior parietal cortex supports elementary functions that are necessary for multiple object maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiology and neuroimaging evidence specifically links MTL activity to maintenance in working memory. A recent review on single neuron recordings suggested direct involvement of MTL neural firing patterns in working memory (6). Patterns of neural activity were consistent to specific predictions from Cowan’s activated long-term memory model of working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been proposed for the implementation of working memory capabilities in neural networks. They have been divided into three categories: classical persistent activity, activity silent, and dynamic coding [13]. While models based on persistent activity do not engage any synaptic plasticity mechanism [14], activity-silent models and some dynamic coding models exploit short-term synaptic plasticity or neuronal adaptation [15]- [17].…”
Section: Related Workmentioning
confidence: 99%